Класифікація та комплексна цінність стану торгово-розважальних центрів: проектно-орієнтований підхід - Рак, Юрій Павлович; Головатий, Р. Р. (НТУ "ХПІ", 2016)
Проведено аналіз стану реалізації проектів об‘єктів торгово-розважальних центрів з позиції підвищення рівня безпеки життєдіяльності та запропоновано означення «Торгово-розважальний центр», «Торгово-розважальний комплекс» та «Комплексна цінність торгово-розважальних центрів». Виконана класифікація торгово-розважальних центрів за класифікаційними ознаками та критеріями, що характеризують підвищений стан безпеки та привабливість при їх експлуатації.

Was done the analysis of projects objects of trade and entertainment centers from the perspective of improving the life safety and is proposed the definition of "Trade and entertainment center", "Trade and entertainment center" and "Complex value of trade and entertainment center." A classification of shopping centers on the classification criteria and the criteria are characterized by increased security status and attractiveness of their operation. The classification of trade and entertainment centers on the criteria of classification features were made. It characterizes the security situation and will increase the attractiveness in their operation. In the nearest future the most secure and modern TEC will be those buildings who will have unique qualities such as safety systems, excellent customer service, and thus by a high level of trust (the client) to the mall. The important role will play those TEC, who have clearly formed valueoriented project management, including communication values using innovative methods and models. Trade and entertainment centers as an organization are included to the complex process of interaction management. They being both as an enterprise that serves the public and satisfying a great range of his interests and architectural site, which is leased and increases the business attractiveness at the district of TEC location. This duality of the essence of TEC center makes difficult to assess the effectiveness of its security.
Classification and complex state value shopping centers, project-oriented approach
Keywords: клас; проекти; безпека; інформаційні технології; trade and entertainment centers; class; classification; projects; value; safety; project-oriented approach; IT